Withania somnifera (L.) Dunal (Ashwagandha); current understanding and future prospect as a potential drug candidate - Bhat, Javeed Ahmad; Akther, Tahira; Najar, Rauf Ahmad; Rasool, Faheem; Hamid, Abid (Frontiers in Pharmacology, 2022)
Cancer and Neurodegenerative diseases are one of the most dreadful diseases to cure and chemotherapy has found a prime place in cancerous treatments while as different strategies has been tested in neurodegenerative disease as well. However due to adverse shortcomings like resistance of cancerous cells and inefficiency in neurodegenerative disease, plant sources have always found a prime importance in medicinal use for decades, Withania somnifera (L.) Dunal (W. somnifera) is one such well-known plant having medicinal use reported since centuries. It is commonly known as winter cherry or ashwagandha and is a prime source of pharmaceutically active compounds withanolides. In recent years research is being carried in understanding extensive role of W. somnifera in cancer and neurological disorders. W. somnifera has been reported to be beneficial in DNA repair mechanisms; it is known for its cellular repairing properties and helps to prevent the apoptosis of normal cells. This review summarizes the potential properties and medicinal benefits of W. somnifera especially in cancer and neurodegenerative diseases. Available data suggest that WS is effective in controlling disease progressions and could be a potential therapeutic target benefiting human health status. The current review also discusses the traditional medicinal applications of W. somnifera, the experimental evidence supporting its therapeutical potential as well as obstacles that necessitate being overcome for W. somnifera to be evaluated as a curative agent in humans. Keywords: Withania Sominifera (W. somnifera), Cancer, Neurodegenerative Disorders, Alzheimer’s disease, and stroke